2010
DOI: 10.1177/1933719110364248
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Screening for Risk Loci of Idiopathic Recurrent Miscarriage in a Han Chinese Population: A Pilot Study

Abstract: The etiology of recurrent miscarriage (RM) is extremely heterogeneous, including genetic, immunologic, anatomic, endocrinological, and infectious anomalies. About 50% of RM is unexplained or poorly understood, which is called idiopathic recurrent miscarriage (IRM). The primary aim of this study was to identify the genetic loci that might be susceptible to IRM. Forty-four Han Chinese patients with IRM during the first trimester of their pregnancies and 44 healthy sex- and ethnic-matched controls were enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 60 publications
2
14
1
1
Order By: Relevance
“…None of these variants were genomewide significant in either the sporadic or recurrent miscarriage analysis, and only 14 (4.2%) and 11 (3%) were nominally significant (P<0.05) in the respective analyses ( Supplementary Table 4). Two genome-wide linkage scans, one of 44 recurrent miscarriage cases and 44 controls and the other of 38 sibling pairs affected by idiopathic recurrent miscarriage reported loci on 6q27, 9q33.1, Xp22.1 23 and 3p12.2, 9p22.1 and 11q13.4 14 as associated with idiopathic recurrent miscarriage but none of the recurrent or sporadic miscarriage associations identified in our much larger analysis overlap with these previously reported regions.…”
supporting
confidence: 51%
“…None of these variants were genomewide significant in either the sporadic or recurrent miscarriage analysis, and only 14 (4.2%) and 11 (3%) were nominally significant (P<0.05) in the respective analyses ( Supplementary Table 4). Two genome-wide linkage scans, one of 44 recurrent miscarriage cases and 44 controls and the other of 38 sibling pairs affected by idiopathic recurrent miscarriage reported loci on 6q27, 9q33.1, Xp22.1 23 and 3p12.2, 9p22.1 and 11q13.4 14 as associated with idiopathic recurrent miscarriage but none of the recurrent or sporadic miscarriage associations identified in our much larger analysis overlap with these previously reported regions.…”
supporting
confidence: 51%
“…This has restricted their efficient use in clinical studies. Genome-wide scan-based studies have been reported, although they have not reached the classical accepted statistical threshold for significance and have apparently failed to identify specific genes [12,13]. Such failure to identify RSA aetiological genes might be explained by the fact that reproduction's inherent complexity theoretically implies that mutations in hundreds of candidate genes may be responsible for the phenotype [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…These differentially expressed genes were found to be associated with defective cell growth, thus suggesting their implication in implantation failure in women with unexplained RM. Wang et al performed a case-control and genome-wide study, and analyzed 430 polymorphic microsatellite markers [62]. Three loci -6q27, 9q33.1 and Xp22.11 -were found to be significantly associated with RM.…”
Section: Genome-wide Studiesmentioning
confidence: 98%